2011
DOI: 10.1371/journal.pone.0018597
|View full text |Cite
|
Sign up to set email alerts
|

The T7-Related Pseudomonas putida Phage φ15 Displays Virion-Associated Biofilm Degradation Properties

Abstract: Formation of a protected biofilm environment is recognized as one of the major causes of the increasing antibiotic resistance development and emphasizes the need to develop alternative antibacterial strategies, like phage therapy. This study investigates the in vitro degradation of single-species Pseudomonas putida biofilms, PpG1 and RD5PR2, by the novel phage ϕ15, a ‘T7-like virus’ with a virion-associated exopolysaccharide (EPS) depolymerase. Phage ϕ15 forms plaques surrounded by growing opaque halo zones, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
146
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(152 citation statements)
references
References 60 publications
6
146
0
Order By: Relevance
“…In a previous study (unpublished data), we found that the plaques of the bacteriophages F770/05, F510/08 and F1245/ 05 were surrounded by growing opaque halo zones, which could be related to the presence of a virion-associated exopolysaccharide depolymerase (Cornelissen et al, 2011). This and related enzymes have been found to enhance the biofilm-eradicating activity of bacteriophages compared with non-depolymerase-producing bacteriophages (Hughes et al, 1998).…”
mentioning
confidence: 70%
“…In a previous study (unpublished data), we found that the plaques of the bacteriophages F770/05, F510/08 and F1245/ 05 were surrounded by growing opaque halo zones, which could be related to the presence of a virion-associated exopolysaccharide depolymerase (Cornelissen et al, 2011). This and related enzymes have been found to enhance the biofilm-eradicating activity of bacteriophages compared with non-depolymerase-producing bacteriophages (Hughes et al, 1998).…”
mentioning
confidence: 70%
“…There is no indication from the sequence analysis that RIO-1 can be temperate; hence, we do not believe that the turbid zones come from that source. Other precedented causes of turbid lysis zones include phage-borne or phage-produced enzymes that attack host extracellular polymers (56), feeding of hosts by phage metabolites (57), or lysis inhibition related to superinfection (58).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, immediately surrounding the AB-Army1 plaque, there was a large zone of AB5075 that was phenotypically distinct from AB5075 in the adjacent lawn. Halos of this kind implicate a diffusible phage-encoded protein causing an enzymatic change to the surface of the bacteria, a well-recognized phenomenon of phages that infect capsular bacteria (37)(38)(39)(40)(41)(42)(43)(44). An efficiency-of-plating assay showed that when a dilution series from 10 10 to 10 2 of AB-Army1 was spotted on an overlay plate of AB5075, AB-Army1 could infect at a concentration as low as 10 2 PFU per ml.…”
Section: Characterization Ofmentioning
confidence: 99%